PKM Gambaran pengetahuan dan sikap terhadap pencegahan COVID-19 pada masyarakat Desa Watumea, Kecamatan Eris, Kabupaten Minahasa - Palandeng, Henry; Layuck, Anggun R. P.; Pratasik, Chealsea; Rapar, Elsani P. R.; Dotulong, Dean (Jurnal Kedokteran Komunitas dan Tropik, 2024)
Community knowledge and attitudes towards the COVID-19 virus in Watumea Village, Eris Subdistrict, Minahasa Regency have not been able to reduce the impact of risks that can lead to increased COVID-19 morbidity and mortality. This study aims to assess the level of knowledge and attitudes towards COVID-19 prevention in reducing the risk of disease, premature death and disability in the future. This study was conducted for 6 months with a total sample size of 45 people. The research method is descriptive research with a cross-sectional research design, and uses a simple random sampling research method. In this study, the measuring instrument used was a questionnaire about knowledge, attitudes towards preventing COVID-19 which consisted of 30 question results: Based on the research, it was found that most of the people of Watumea Village, Eris Subdistrict, Minahasa Regency had good knowledge, positive attitudes and good actions towards COVID-19 prevention. Conclusion: the people of Watumea Village, Eris Subdistrict, Minahasa Regency showed good knowledge, positive attitudes, and good actions towards COVID-19 prevention. Keywords: Knowledge, attitude, COVID-19 prevention, community